Linux Security Cookbook - Barrett, Daniel J. (O'Reilly, 2011)
The Linux Security Cookbook includes real solutions to a wide range of targeted problems, such as sending encrypted email within Emacs, restricting access to network services at particular times of day, firewalling a webserver, preventing IP spoofing, setting up key-based SSH authentication, and much more. With over 150 ready-to-use scripts and configuration files, this unique book helps administrators secure their systems without having to look up specific syntax.